Oblivious transfer based on physical unclonable function system - Yuan-bo GUO; Zi-nan ZHANG; Kui-wu YANG (Tongxin xuebao)
Oblivious transfer (OT) is a fundamental protocol in cryptography. According to the analysis of physical un-clonable function, a physical unclonable function system framework was defined, and a novel oblivious transfer (POT, PUFS based OT) protocol was proposed based on this framework. Finally, a security analysis of this POT protocol in the universal composition framework was given in detail. Compared with the traditional public key encryption OT scheme, POT protocol does not use any computational assumptions but rather the secure property of PUFS, and thus this scheme needs less computation and communication cost.